2022
DOI: 10.3390/ijms231911332
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypomagnesemia and Liver Injury, Role of Gut-Barrier Dysfunction and Inflammation: Efficacy of Abstinence, and 2-Week Medical Management in Alcohol Use Disorder Patients

Abstract: (1) We investigated the involvement of serum magnesium level in early alcoholic liver disease (ALD), gut barrier dysfunction, and inflammation in alcohol use disorder (AUD) patients; and lastly, the efficacy of 2-week abstinence and medical management to alleviate hypomagnesemia. (2) Forty-eight heavy drinking AUD patients (34 males (M)/14 females (F)) participated in this study. Patients were grouped by serum alanine aminotransferase (ALT) level (a marker of liver injury) as group 1 (Group 1 (Gr.1); ALT ≤ 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previously, we found that hypomagnesemia in the early stages of alcohol-associated liver disease could be one of the factors leading to progression of the disease [3]. In our subsequent clinical longitudinal study on early-stage ALD, we found that magnesium levels could be a valuable indicator of liver cell death and the recovery of liver health with standard of care magnesium supplementation in AUD patients with early-stage liver disease [7]. In this study, we found that there could be a deficiency level of magnesium that would provide vital clues for the detection of AH.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Previously, we found that hypomagnesemia in the early stages of alcohol-associated liver disease could be one of the factors leading to progression of the disease [3]. In our subsequent clinical longitudinal study on early-stage ALD, we found that magnesium levels could be a valuable indicator of liver cell death and the recovery of liver health with standard of care magnesium supplementation in AUD patients with early-stage liver disease [7]. In this study, we found that there could be a deficiency level of magnesium that would provide vital clues for the detection of AH.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier, we reported that such levels of magnesium (sub-clinical) are also present in AUD patients with early-stage ALD or no liver injury [7], thus such levels may not conclude differentiating AUD patients who may have AH or not in an initial clinical review of laboratory charts. We know that when the severity of alcohol-associated liver disease is higher, the homeostasis of magnesium is altered [26].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations